Karate, Taekwondo, Aikido, Kung Fu, Yoga and Other Far Eastern Forms of Activities: Best Method of Treatment of Locomotor’s System Deformities Especially of the So-Called Idiopathic Scoliosis - Karski, Tomasz; Karski, Jacek (Research Highlights in Disease and Health Research Vol. 2, 2023)
The so-called idiopathic scoliosis [adolescent idiopathic scoliosis-AIS] is very common in Poland (till 8%) and in every county in Europe and in America. Many children are operated, mostly because of cosmetic reasons and curve more that 40 degree. The study presents an example of so called idiopathic scoliosis and the principles of treatment. According to our knowledge the cause of deformities in children, youth and pain syndromes in adults are connected not with “Weak muscles” but with 1/ the wrong position of joints of the lower or upper extremities, in the spine, in the whole trunk, 2/ with limited movement of joints, 3/ even connected with pathological position of joint, with contractures in the spine, in the hips, in the knees and in the feet. The study observations confirm that without any doubt the “weak muscles” are not the cause of deformations of children and youth as well, pain syndromes in adults. Unfortunately, the diagnosis of “weak muscles” is very often given / stated by Polish physiotherapist and rehabilitations doctors.